Wide variety of recombinant strains of norovirus GII in pediatric patients hospitalized with acute gastroenteritis in Thailand during 2005 to 2015 - Kanittapon Supadej (2018)
© 2017 Norovirus (NoV) has been reported as being a common cause of acute gastroenteritis both in children and adults worldwide. Of the many variants, NoV GII.4 is the most predominant genotype. One of the mechanisms that drives the evolution and emergence of new variants of NoV is homologous recombination. This study describes the genetic recombination involved in cases of NoV GII detected in pediatric patients with acute gastroenteritis in Chiang Mai, Thailand during 2005 to 2015. From a total of 1938 stool samples, 3 (0.15%) were positive for NoV GI and 298 (15.38%) were identified as NoV GII. The genotypes detected in this study were GI.6, GI.14, GII.1, GII.2, GII.3, GII.4, GII.6, GII.7, GII.12, GII.13, GII.14, GII.15, GII.16, GII.17, GII.20, and GII.21. The NoV recombinant strains were verified by analysis of the partial sequence of ORF1 (RdRp)/ORF2 (capsid) junction. Phylogenetic analyses of partial ORF1 and ORF2 regions resulted in the identification of 21 (6.98%) NoV recombinant strains. Among these, 9 recombination patterns were detected in this study; GII.Pe/GII.4, GII.Pg/GII.1, GII.Pg/GII.12, GII.P7/GII.6, GII.P7/GII.14, GII.P12/GII.4, GII.P16/GII.2, GII.P16/GII.13, and GII.P21/GII.3. The findings demonstrated the wide variety of recombinant strains of NoV GII strains detected in pediatric patients admitted to the hospitals with acute gastroenteritis in Chiang Mai, Thailand during the past decade.